The Role of Digital Forensic Experts in Cybercrime Investigations in Indonesia Based on The Scopus Research Index - Subektiningsih, Subektiningsih; Hariyadi, Dedy (Forum Kerjasama Pendidikan Tinggi, 2022)
The development of information technology, besides having a positive impact, has negative impacts, such as an increase in cybercrime. Several parties are involved in handling cybercrimes in Indonesia, including expert witnesses in digital forensics. It is hoped that cybercrimes can be uncovered through a digital forensic approach. Research related to cybercrime and Digital Forensics in Indonesia is experiencing increasing growth from 2010 to 2021. A very rapid increase was shown in 2017. Through bibliometric analysis, you can analyze expert witnesses in the field of digital forensics by region in Indonesia, such as Sumatera, Western Java, Central Java, and Eastern Java. An expert witness in digital forensics must have technical skills in operating digital forensic tools and analysis and academic skills in uncovering crimes. The results of this study are very useful for law enforcement officers or lawyers in determining expert witnesses in the field of digital forensics. List of digital forensic experts in Indonesia who have been tested from their scientific studies by conducting various paper publications. So, law enforcement can synergize with digital forensic experts to solve cybercrime. One of the roles of a digital forensic expert is as an expert witness in court. Through research, it is hoped that there will be an increase in awareness of digital forensic experts to conduct scientific publications so that it is easier to be recognized by law enforcement and academics for updating methods and techniques of cybercrime investigation